ADVANCEMENTS IN EXPLORING CARDIAC MORPHOLOGY: INNOVATIVE TECHNIQUES AND INSIGHTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The investigation of cardiac morphology has undergone a transformative evolution due to recent technological progress. This article delves into fresh methodologies and tools for scrutinizing the intricacies of the heart, equipping researchers and healthcare providers with unparalleled insights. We examine the application of state-of-the-art technologies such as 3D printing, immersive virtual reality, cutting-edge imaging modalities, cardiac biomarkers, and electrophysiological mapping in the exploration of cardiac anatomy. By amalgamating these approaches, a comprehensive grasp of the heart's structural intricacies is achieved, resulting in amplified diagnostic and therapeutic strategies for conditions such as arrhythmias, myocardial infarctions, and valvular heart diseases.